4 - Experiences in New Public Management in Africa: The Case of Performance Management Systems in Botswana - Dzimbiri, Lewis B. (Africa Development, 2021)
In his 18-page paper entitled ‘The Challenges of Governance, Public Sector Reform and Public Administration in Africa: Some Research Issues’, Guy Mhone made central to public sector reforms the need to promote procedural rationality in the operation of the public sector and instrumental rationality in terms of economic, social and political outcomes. The present paper contributes to the debate on procedural rationality by focusing attention on performance manage- ment systems (PMS), which has emerged with the advent of New Public Man- agement (NPM). It starts by providing the context of the changing role of the state since the 1980s as a background to public sector reforms in Africa. The paper further clarifies NPM and PMS as applied to the public sector before going on to discuss the experience of Botswana in public sector reforms, with particular emphasis on its performance management system. How PMS emerged, its implementation, its monitoring and evaluation are examined in this paper, along with an analysis of challenges and lessons learnt.